Rezolvați ecuația: 1 + {2 + 3 × [4 + 5 × (6 − x)] : 7} : 8 = 2
Răspunsuri la întrebare
Răspuns de
0
Răspuns:
Explicație pas cu pas:
1 + {2 + 3 × [4 + 5 × (6 − x)] : 7} : 8 = 2
{2 + 3 × [4 + 5 × (6 − x)] : 7} : 8 = 2 - 1 = 1
2 + 3 × [4 + 5 × (6 − x)] : 7 = 1 × 8 = 8
3 × [4 + 5 × (6 − x)] : 7 = 8 - 2 = 6
3 × [4 + 5 × (6 − x)] = 6 × 7 = 42
4 + 5 × (6 − x) = 42 : 3 = 14
5 × (6 − x) = 14 - 4 = 10
6 - x = 10 : 5 = 2
x = 6 - 2 = 4
Alte întrebări interesante
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă